Local perceptions, attitudes, beliefs, and practices toward bird-window collisions in Monteverde, Costa Rica (UNED Research Journal, 2018)
Bird-window collisions are an important cause of bird mortality worldwide. Reducing collisions requires understanding of the costs and benefits perceived by stakeholders. I consulted two focus groups, conducted 18-semi-strcutured interviews and applied surveys to 58 residents of Monteverde, Costa Rica, to understand their perception of the problem. Many reported collisions in their houses but there is a lack of information about the magnitude of the situation. Black silhouettes are the most frequent method of prevention, even though they are mostly ineffective. The main factors for selecting methods include unblocked views, aesthetics, effectiveness, ease of installation and removal, and ease of maintenance. The preferred effective method was cords (Acopian Bird Savers), and painted dots was the least liked. I recommend education about effective methods for Monteverde and similar communities.
Keywords: bird-building collisions; methods to prevent collisions; bird mortality; Green building design; bird-friendly buildings